2018
DOI: 10.1200/jgo.18.00058
|View full text |Cite
|
Sign up to set email alerts
|

Detection of High-Risk Human Papillomavirus in Oral Cavity Squamous Cell Carcinoma Using Multiple Analytes and Their Role in Patient Survival

Abstract: Purpose Accurate detection of human papillomavirus (HPV) in oral cavity squamous cell carcinoma (OSCC) is essential to understanding the role of HPV in disease prognosis and management of patients. We used different analytes and methods to understand the true prevalence of HPV in a cohort of patients with OSCC with different molecular backgrounds, and we correlated HPV data with patient survival. Methods We integrated data from multiple analytes (HPV DNA, HPV RNA, and p16), assays (immunohistochemistry, polyme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 52 publications
6
38
0
Order By: Relevance
“…In the current study, two of the HPV DNA-negative samples revealed positive HPV16 viral transcripts. A previous study by Palve et al [52] also found three cases with HPV E6/E7 RNA and negative HPV DNA results. This was justified by the possibility that the DNA in such tumors was degenerated and hence could not act as a proper template for DNAdependent tests.…”
Section: Discussionmentioning
confidence: 77%
“…In the current study, two of the HPV DNA-negative samples revealed positive HPV16 viral transcripts. A previous study by Palve et al [52] also found three cases with HPV E6/E7 RNA and negative HPV DNA results. This was justified by the possibility that the DNA in such tumors was degenerated and hence could not act as a proper template for DNAdependent tests.…”
Section: Discussionmentioning
confidence: 77%
“…Although HPV‐positive OPSCC shares similarities with early‐onset OTSCC in terms of the overall mutation rate, HPV‐positive OPSCC specimens tend to have infrequent TP53 or CDKN2A mutations 27 . Several studies have looked for possible involvement of HPV in OTSCC, but results have shown that only approximately 5% of OTSCC specimens have detectable HPV 9,41,42 . In addition, broader transcriptome searches for other possible viruses have yet to yield any substantive results 9 .…”
Section: Discussionmentioning
confidence: 99%
“…27 Several studies have looked for possible involvement of HPV in OTSCC, but results have shown that only approximately 5% of OTSCC specimens have detectable HPV. 9,41,42 In addition, broader transcriptome searches for other possible viruses have yet to yield any substantive results. 9 Thus, the underlying cause for the rise in early OTSCC remains enigmatic.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors targeting epidermal growth factor receptor (EGFR)-regulated pathways, Vascular endothelial growth factor (VEGF) pathway, multiple kinases, PI3-K/AKT/mTOR pathway, and other novel targets, in a combined modality treatment with immunotherapy, are likely to increase therapeutic efficacy in patients with HNSCC (Matta & Ralhan, 2009; Kaidar-Person, Gil & Billan, 2018). Except for oropharyngeal tumors, human papillomavirus (HPV) is rare in oral cavity tumors (Palve et al, 2018). Its role in risk stratification is still under clinical trial evaluations in non-oropharyngeal tumors.…”
Section: Introductionmentioning
confidence: 99%